Present situation and future potential of cassava in Malaysia - Tan, Swee Lian; Idris, Khatijah (International Center for Tropical Agriculture, 2001)
In Malaysia, the processing of sago starch predates that of cassava, having been established before 1416. With its introduction, cassava, which is a much shorter term crop, quickly replaced sago palm as the preferred raw material among starch processors. Hence, except for a small amount serving the fresh food market, cassava is planted in Malaysia mainly for starch processing. The cassava area in Peninsular Malaysia has declined steadily to 1,631 ha in 1997 after peaking in 1976 at 20,913 ha. This decline is due to the curbing of illegal cultivation; land alienation policy with a bias against cassava; switching from cassava to more lucrative crops; rising costs of production; low prevailing price for cassava roots; and competition for land for agricultural and non-agricultural activities during the economic boom prior to July 1997. Of the eight starch factories reported in Perak in 1984, only two are still in operation. Recently, in Sabah, a starch factory opened to process roots supplied through contract farming from an area of more than 3,000 ha. In trade, cassava starch takes the form of flour, flakes, pearls and starch powder. There is a growing demand for starch with imports amounting to 88,210 tonnes in 1997. Most of this starch is used in food industries, particularly for making monosodium glutamate (using about 3,000 tonnes of starch per month). Other significant users are manufacturers of glucose, bakery and biscuit products, textiles and paper. There is also increasing interest in growing edible varieties of cassava for processing into snacks. The future potential in terms of domestic demand for cassava starch is very good. Since the onset of the economic downturn faced by Southeast Asia, the Malaysian government has actively encouraged agriculture (to offset the country’s huge food import bill amounting to almost US$ 2.9 billion a year) by providing easier access to farmland. There is recent renewed enthusiasm for planting cassava for production of starch, dried chips for livestock feed and sweeteners (high fructose glucose syrup or HFGS). For large-scale mechanized cassava production, certain prerequisites of soil type, terrain, climate and farm size matching the factory’s capacity, must be satisfied. While land is hard to come by in Peninsular Malaysia, more than 80,000 ha of land are still available in Sabah. Starch is the most likely product to be feasible and profitable in the immediate future compared to dried chips and HFGS production, because of a high demand in the local market, and a well-established technology for starch processing. Stable, high-yielding varieties with intermediate to high starch content to ensure higher starch recovery are required; better still if they can be harvested early. The potential of using cassava as a carbohydrate-rich animal feedstuff is promising, but being low in protein compared to maize, additional protein is required from another source, entailing extra costs. Also, it is costly to dry cassava by artificial means. Although it is technically possible to produce HFGS from cassava, it involves converting starch by enzymatic processes – a complicated and expensive procedure. This does not seem economically feasible in the immediate future, given the current low world price for sugar. Instead, modified starches and their products have very good future potential as profitable agro-based industries. Modification of starches not only expands their scope of utilization by altering their physico-chemical characteristics, but also increases their value as compared to native starch. An alternative use of cassava, which has some prospects, is the production of snack foods. Although oil-fried crisps and crackers are traditional snacks produced by cottage industries, only recently have attempts been made by larger food processors to improve their quality and packaging, and to target the more up-market urban consumer and overseas market. Preliminary work at MARDI has shown that cassava makes a very good raw material for extruded snacks.